Delivery of Healthcare Resources Using Autonomous Ground Vehicle Convoy Systems: An Overview - Cheung, Calvin; Mohammadi, Alireza; Rawashdeh, Samir; Baek, Stanley (Frontiers in Robotics and AI, 2021)
Utilizing military convoys in humanitarian missions allows for increased overall performance of healthcare logistical operations. In order to properly gauge performance of autonomous ground convoy systems in military humanitarian operations, a proper framework for comparative performance metrics needs to be established. Past efforts in this domain have had heavy focus on narrow and specialized areas of convoy performance such as human factors, trust metrics, or string stability analysis. This paper reviews available Army doctrine for manned convoy requirements towards healthcare missions and establishes a framework to compare performance of autonomous convoys, using metrics such as spacing error, separation distance, and string stability. After developing a framework of comparison for the convoy systems, this paper compares the performance of two autonomous convoys with unique convoy control strategies to demonstrate the application and utility of the framework.